Multiple-image encryption algorithm based on mixed image element and chaos. (August 2017) - Zhang, Xiaoqiang; Wang, Xuesong
Highlight: A new multiple-image encryption algorithm based on mixed image element and chaos is proposed. Conceptions of pure and mixed image elements are defined. A similar algorithm is introduced and the comparison analyses are made. Experimental results show that the proposed algorithm is efficient and secure. Abstract: To improve the encryption efficiency and facilitate the secure transmission of multiple images, this paper presents a new multiple-image encryption (MIE) algorithm based on the mixed image element and piecewise linear chaotic maps (PWLCM). Firstly, Alice (the sender) combines original images into a big image, and divides it into many pure image elements; secondly, she scrambles these pure image elements with the chaotic sequence generated by the PWLCM system to get mixed image elements; thirdly, she combines these mixed image elements into a big-scrambled image, and segments it into small images with the equal size of original images; finally, these small images, i.e., encrypted images, are named with the filenames generated by another PWLCM system. Meanwhile, the comparison analysis with a similar existing algorithm is made. Experimental results and algorithm analyses show that the new algorithm is very efficient and secure. Graphical abstract: